The Narrative Elements of Islamic Resistance to Terrorism Issues in The Movie Bulan Terbelah Di Langit Amerika - Safira, Deina; Kurniawan, Donie Fadjar; Al-Hamzi, Ali Mohammed Saleh; Yudhitya, Roudlotul Jannati Rochnadia Noorva (Capture : Jurnal Seni Media Rekam, 2023)
The film Bulan Terbelah di Langit Amerika, which raises the issue of terrorism related to Islam, received a good response from Indonesian audiences. This research aims to identify the narrative elements, including plot, storyline, characters, and character functions, concerning the Islamic resistance against the issue of terrorism depicted in the film Bulan Terbelah di Langit Amerika. This research employed qualitative research methods to determine the meaning behind a phenomenon. Data for this research were collected through the observation of the film Bulan Terbelah di Langit Amerika. The results of this study indicate that the narrative elements in the film, encompassing plot, storyline, characters, and character functions, effectively portray Islamic resistance to the issue of terrorism. The analysis of the plot storyline in the seven key scenes demonstrates the issue of terrorism and Islamic resistance, which is depicted through dialogue, facial expressions, and body gestures of the movie players. The results of this study can motivate young filmmakers who want to produce Islamic-themed films with a different perspective. Keywords: narrative, terrorism issue, Islam, Bulan Terbelah di Langit Amerika.